Affective Assessment Dynamics in Islamic Education: A Public and Private High School Comparative Study - Muhammad Ridho Ramadhan; Saepul Anwar; Pandu Hyangsewu (AFKARINA: Jurnal Pendidikan Agama Islam, 2026)
This study investigates the dynamics of planning, implementing, and utilizing affective assessments in Islamic Religious Education (IRE) across divergent institutional contexts, addressing the "utilization blindspot" where affective data is frequently reduced to administrative formalities. Employing a qualitative multiple-case study design, this research was conducted at a public and a private senior high school. Data, gathered through in-depth interviews, participant observations, and document analysis involving IRE teachers, were evaluated using the Interactive Analysis Model and cross-case synthesis. Findings reveal that despite structural constraints, teachers' profound epistemological grounding in Tazkiyatun Nafs and Muhasabah preserves assessment authenticity. Furthermore, both institutions successfully transformed affective data into active formative feedback loops (Assessment for Learning) and established targeted tripartite pastoral care systems involving teachers, homeroom teachers, and parents. This study concludes that effective affective assessment transcends bureaucratic compliance, functioning as a transformative catalyst for continuous moral character development. Consequently, it is recommended that educational policymakers formulate adaptive administrative guidelines to structurally support authentic character evaluation.